Relationship between long non-coding RNA polymorphism and the risk of coronary artery disease: A protocol for systematic review and meta-analysis. Issue 12 (26th March 2021) - Wang, Bolin; Su, Zhihui; Wan, Lijun; He, Tao
Abstract: Background: Previous epidemiological studies displayed that long non-coding RNA (LncRNA) polymorphisms are associated with an increased risk of coronary artery disease, while the results are inconsistent. Therefore, we conducted a meta-analysis to more accurately determine the association between LncRNA polymorphism and the risk of coronary artery disease. Methods: PubMed, EmBase and Web of Science databases were searched, and the time to build the database was set until December 2020. The association between LncRNA polymorphism and the risk of coronary artery disease was collected and evaluated. Meta-analysis was performed by STATA 14.0 software, and the odds ratio and its 95% confidence interval (95%CI) were applied to estimate the association between LncRNA polymorphism and the risk of coronary artery disease. Results: The results of this meta-analysis will be submitted to a peer-reviewed journal for publication. Conclusion: This meta-analysis will summarize the relationship between LncRNA polymorphism and coronary disease risk. Ethics and dissemination: Ethical approval was not required for this study. The systematic review will be published in a peer-reviewed journal, presented at conferences, and shared on social media platforms. This review would be disseminated in a peer-reviewed journal or conference presentations. OSF REGISTRATION NUMBER: DOI 10.17605/OSF.IO/9XPHS.